2002
DOI: 10.1016/s0002-9440(10)64498-7
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Deficiency Leads to Enhanced Neutrophil Migration and Lung Injury in Escherichia coli Pneumonia in Mice

Abstract: CD44 is a major cell-surface receptor for hyaluronic acid (HA), a glycosaminoglycan component of extracellular matrix. HA-CD44 interactions have been implicated in leukocyte extravasation into an inflammatory site. This study examined the role of CD44 in acute inflammatory responses during pneumonias induced by Escherichia coli and Streptococcus pneumoniae using CD44-deficient mice. In E. coli-induced pneumonia, neutrophil accumulation in the lungs and edema formation was increased by 84% and 88%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
124
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 54 publications
(38 reference statements)
3
124
0
1
Order By: Relevance
“…In contrast, other investigations did not support an essential role for CD44 in mediating leukocyte infiltration in inflamed tissues, but suggested that CD44-hyaluronan interactions are important for suppression of inflammation and resolution of the inflammatory infiltrate. CD44 KO animals exhibited accentuated inflammation in a model of collagen-induced arthritis (28), were more susceptible to endotoxin-induced shock (29), and showed enhanced neutrophil migration and lung injury in murine bacterial pneumonia (30). In vitro experiments demonstrated that CD44 Ϫ/Ϫ neutrophils migrate faster through matrigel than WT neutrophils, suggesting that CD44 may slow neutrophil migration through extracellular matrix (30).…”
Section: The Role Of Cd44 In Regulation Of the Postinfarction Inflammmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, other investigations did not support an essential role for CD44 in mediating leukocyte infiltration in inflamed tissues, but suggested that CD44-hyaluronan interactions are important for suppression of inflammation and resolution of the inflammatory infiltrate. CD44 KO animals exhibited accentuated inflammation in a model of collagen-induced arthritis (28), were more susceptible to endotoxin-induced shock (29), and showed enhanced neutrophil migration and lung injury in murine bacterial pneumonia (30). In vitro experiments demonstrated that CD44 Ϫ/Ϫ neutrophils migrate faster through matrigel than WT neutrophils, suggesting that CD44 may slow neutrophil migration through extracellular matrix (30).…”
Section: The Role Of Cd44 In Regulation Of the Postinfarction Inflammmentioning
confidence: 99%
“…CD44 KO animals exhibited accentuated inflammation in a model of collagen-induced arthritis (28), were more susceptible to endotoxin-induced shock (29), and showed enhanced neutrophil migration and lung injury in murine bacterial pneumonia (30). In vitro experiments demonstrated that CD44 Ϫ/Ϫ neutrophils migrate faster through matrigel than WT neutrophils, suggesting that CD44 may slow neutrophil migration through extracellular matrix (30). These actions may be due to CD44-induced intracellular signaling events in leukocytes bound to hyaluronan or other ligands (30).…”
Section: The Role Of Cd44 In Regulation Of the Postinfarction Inflammmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, CD44 expressed on hemopoietic cells is an important regulator of LPS-TLR signaling in macrophages, affecting pulmonary inflammatory response and PMN recruitment [9]. However, although intratracheal LPS [9] or intrapulmonary E. coli [18] challenge of CD44 −/− mice resulted in an exaggerated inflammatory response, none of this was found by us after an intramammary challenge (Gonen E. and Shpigel N.Y., unpublished results). Furthermore, although there is ample evidence for the possible role of CD44 in PMN extravasation, interstitial migration, and trans-epithelial migration, PMN recruitment was unaffected by CD44 deficiency in Figure 3.…”
Section: Discussionmentioning
confidence: 78%
“…In CD44-deficient mice, there was actually enhanced neutrophil migration to lung upon infection with E. coli (Wang et al, 2002). Blockade of CD18 integrins inhibits migration of neutrophils into the lung in response to experimental Pseudomonas aeruginosa and E. coli/lipopolysaccharide, as well as IgG immune-complex deposition, IL-1 and phorbol myristate acetate.…”
Section: Discussionmentioning
confidence: 99%